SPANISH WAVE 3. Pre-election Study - Lobo, Marina Costa (2020)
This study is part of the MAPLE Project, ERC – European Research Council Grant, 682125, which aims to study the Politicisation of the EU before and after the Eurozone Crisis in Belgium, Germany, Greece, Ireland, Portugal and Spain. In each of these countries an online panel will be carried out just before and just after the legislative elections. This Report pertains to the pre-election survey of Spain Legislative elections 2019. Our questionnaire seeks to model the political context of political choices, and to understand the importance that European attitudes may have in voting behaviour. In Spain, we have partnered with Netquest. In this report we present a number of political attitudes broken down by partisanship in Spain. We are interested in the way in which partisan preferences are related to political attitudes, including national as well as EU issues. The target population is the General voting population aged >18 years old. The sample size is 3.007. The fieldwork was done using the Netquest online panel and took place between 27/03/2019 and 12/04/2019. The sample was designed using data from the Census 2011 to create a socio demographic matrix which crossed four variables: gender (male, female); age (18- 24; 25-54; 55+); education (up to secondary; secondary, more than secondary), region (Noroeste, Noreste, Comunidad de Madrid, Centro, Este, Sur and Canarias). The resulting dataset was weighted according to a weight combining gender (male, female), age (18-24; 25-54; 55-64; 65+) and education up to secondary; secondary, more than secondary), using, also in this case, data from the 2011 Spanish Census. To identify respondents’ partisanship we used the following procedure: the respondent was asked if s/he felt close to a party. To those who replied “no” in this question, they were asked if they felt closer to one party in particular. Those who repeated “no” in this second question were coded as “without party id”. All others were presented with a list of political parties from which they could choose the one they identified with. In this report, we only take into consideration parties which at least 5% of respondents identify with. One-way ANOVA analysis was performed to check whether the differences between party means are statistically significant. On national issues, differences tend to be significant between the left and the right party group, but not within them. On European issues the pattern is not so clear. Differences tend to be significant between PP, PSOE and Ciudadanos, vis a vis VOX, IU and Podemos. The results can be provided on request.